2012
DOI: 10.1007/s10047-012-0681-1
|View full text |Cite
|
Sign up to set email alerts
|

Poly(2-methacryloyloxyethyl phosphorylcholine)-grafted highly cross-linked polyethylene liner in primary total hip replacement: one-year results of a prospective cohort study

Abstract: To control particle-induced osteolysis in total hip replacement (THR), we developed a new technique to graft poly(2-methacryloyloxyethyl phosphorylcholine) onto the surface of polyethylene liners. A prospective cohort study was conducted to investigate the clinical safety of this novel bearing surface. Between April 2007 and September 2008, we recruited a prospective consecutive series of 80 patients in five participating hospitals. These patients received a cementless THR; a 26-mm-diameter cobalt-chromium-mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…For a life-long acetabular liner in an artificial hip replacement, we have recently developed an articular-cartilage-inspired technology for surface modification with grafting of poly(2-methacryloyloxyethyl phosphorylcholine [MPC]) (PMPC) [17][18][19][20][21]. A nanometer-scale surface modification layer of PMPC was formed on a CLPE surface to recreate the ideal hydrophilicity and lubricity of a physiological joint surface, which achieved levels that were similar to those of articular cartilage [22][23][24].…”
Section: Introductionmentioning
confidence: 95%
“…For a life-long acetabular liner in an artificial hip replacement, we have recently developed an articular-cartilage-inspired technology for surface modification with grafting of poly(2-methacryloyloxyethyl phosphorylcholine [MPC]) (PMPC) [17][18][19][20][21]. A nanometer-scale surface modification layer of PMPC was formed on a CLPE surface to recreate the ideal hydrophilicity and lubricity of a physiological joint surface, which achieved levels that were similar to those of articular cartilage [22][23][24].…”
Section: Introductionmentioning
confidence: 95%
“…However, in vitro findings do not always translate to clinical success. We conducted clinical trials (80 patients) of PMPC-grafted CLPE liners at multiple medical centers between 2007 and 2009 in Japan [35,36]. We observed neither osteolysis nor a need for revision surgery during followup periods of up to 7 years for the clinical trials.…”
Section: Discussionmentioning
confidence: 97%
“…Modification of the bearing surfaces of an artificial joint with a hydrophilic layer should increase lubrication to levels comparable to that provided by articular cartilage under physiological conditions [17,20,21,23]. 2-Methacryloyloxyethyl phosphorylcholine (MPC) polymers are one of the most common biocompatible and hydrophilic polymers that have been clinically applied [13,35,36]. It has been demonstrated that a nanometer-scale layer of PMPC can be formed on a crosslinked PE (CLPE) surface to better reproduce the ideal hydrophilicity and lubricity of the physiological joint surface [18,[20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we prepared a biocompatible polymer layer, i.e., poly (2-methacryloyloxyethyl phosphorylcholine (MPC)) (PMPC). MPC is a methacrylate monomer bearing a phosphorylcholine group, and it can provide various types of polymers upon copolymerization with other vinyl compounds [16][17][18][19][20][21][22][23][24][25]. MPC polymers show great potential for applications in the fields of biomedical science and bioengineering because they possess beneficial properties such as excellent antibiofouling ability and friction suppression.…”
Section: Introductionmentioning
confidence: 99%
“…MPC polymers show great potential for applications in the fields of biomedical science and bioengineering because they possess beneficial properties such as excellent antibiofouling ability and friction suppression. Thus, numerous medical devices, including intravascular stent [24], soft contact lenses [25], artificial heart [19], and artificial hip joint [22,23] have been developed from MPC polymers and applied clinically. The biomedical efficacy and safety of MPC polymers are therefore well established.…”
Section: Introductionmentioning
confidence: 99%